A holistic look at education of the Syrians under temporary protection in Turkey: policy, leadership and practice. Issue 1 (2nd January 2020) - Arar, Khalid; Örücü, Deniz; Ak Küçükçayir, Gülnur
ABSTRACT: We sought to provide a holistic view of education of the Syrians under temporary protection by exploring two schooling models in terms of policy and practice for integration. Relying on social justice (SJ) framework as redistribution, recognition and representation, and on ecological framework, we adopted qualitative phenomenological approach with both interviews with principals and teachers integrating Syrian students and related policy text analysis. Our findings indicated that this is a patchy space although SJ framework is evident in the implementations of the school practitioners. Yet, the existing discrepancy between policy and practice as well as the unsystematic approach in evaluating various implementations leaves the rigor vague. Further conclusions and implications are discussed.